2004
DOI: 10.1086/420988
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Kinematics of Boxy Bulges: Large-Scale Bars and Inner Disks

Abstract: Long-slit stellar kinematic observations were obtained along the major axis of 30 edge-on spiral galaxies, 24 with a boxy or peanut-shaped (B/PS) bulge and six with other bulge types for comparison. Such B/ PS bulges are identified in at least 45% of highly inclined systems, and a growing body of theoretical and observational work suggests that they are the edge-on projection of thickened bars. Profiles of the mean stellar velocity V, the velocity dispersion , as well as the asymmetric (h 3 ) and symmetric (h … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
186
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(221 citation statements)
references
References 77 publications
(192 reference statements)
33
186
2
Order By: Relevance
“…These findings were confirmed by Chung & Bureau (2004), who considered 24 edge-on galaxies with X-shaped structures, and demonstrated that 22 of them show clear kinematic bar signatures. Kinematic identification of X-shaped structures for face-on galaxies was performed in Méndez-Abreu et al (2008).…”
Section: Introductionmentioning
confidence: 54%
“…These findings were confirmed by Chung & Bureau (2004), who considered 24 edge-on galaxies with X-shaped structures, and demonstrated that 22 of them show clear kinematic bar signatures. Kinematic identification of X-shaped structures for face-on galaxies was performed in Méndez-Abreu et al (2008).…”
Section: Introductionmentioning
confidence: 54%
“…As the angular resolution of spectroscopic data has improved, detailed measurements on nearby galaxies have shown in some galaxies an unexpected drop in the stellar velocity dispersion as the nucleus is approached, a phenomenon referred to as a dispersion drop or σ-drop (Emsellem et al 2001;Emsellem 2004). One of the first known examples of this phenomenon can be found in Jarvis et al (1988), later results include those reported by Jarvis & Peletier (1991), Bottema (1993), van der Marel (1994), Bertola et al (1996), Bottema & Gerritsen (1997), Fisher (1997), Simien & Prugniel (1997a,b,c), Héraudeau & Simien (1998), Simien & Prugniel (1998), Héraudeau et al (1999), Simien & Prugniel (2000), Emsellem et al (2001), Simien & Prugniel (2002), de Zeeuw et al (2002, Aguerri et al (2003), Márquez et al (2003), Shapiro et al (2003), Chung & Bureau (2004), Falcón-Barroso et al (2006), Ganda et al (2006), Emsellem et al (2008), and Dumas et al (2007).…”
Section: Introductionmentioning
confidence: 76%
“…It is obviously difficult to unambiguously identify the presence of a bar in nearly edgeon systems. However, about half of disc galaxies demon-strates boxy/peanut-shaped structures in the central region (Lütticke et al (2000); Laurikainen et al (2011)), which is tagged by some authors as projection of the vertical structure of bars (Bureau & Freeman 1999;Chung & Bureau 2004).…”
Section: The Model Dependence Of the Obtained Resultsmentioning
confidence: 99%